2020
DOI: 10.1093/braincomms/fcaa178
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic resonance imaging pattern recognition in childhood bilateral basal ganglia disorders

Abstract: Bilateral basal ganglia abnormalities on MRI are observed in a wide variety of childhood disorders. MRI pattern recognition can enable rationalisation of investigations and also complement clinical and molecular findings, particularly confirming genomic findings and also enabling new gene discovery. A pattern recognition approach in children with bilateral basal ganglia abnormalities on brain MRI was undertaken in this international multicentre cohort study. 305 MRI scans belonging to 201 children with 34 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 93 publications
5
24
0
Order By: Relevance
“…As was the case with our patient, despite the presence of classical radiological changes, there may be a delay in diagnosis for many years in patients with BTBGD, likely due in part to the rarity of this disease, along with an extensive differential diagnoses for bilateral basal ganglia T2 hyperintensity on MRI. One of the top differential considerations in BTBGD is viral encephalitis, particularly Ebstein-Barr virus which also demonstrates multifocal cortical, subcortical, and bilateral deep grey matter T2-FLAIR hyperintensities [8] . Autoimmune-mediated etiologies of encephalitis can also present with bilateral basal ganglia involvement, however some potentially helpful distinguishing features include cortical thickening and involvement of mesial temporal lobes and limbic systems [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As was the case with our patient, despite the presence of classical radiological changes, there may be a delay in diagnosis for many years in patients with BTBGD, likely due in part to the rarity of this disease, along with an extensive differential diagnoses for bilateral basal ganglia T2 hyperintensity on MRI. One of the top differential considerations in BTBGD is viral encephalitis, particularly Ebstein-Barr virus which also demonstrates multifocal cortical, subcortical, and bilateral deep grey matter T2-FLAIR hyperintensities [8] . Autoimmune-mediated etiologies of encephalitis can also present with bilateral basal ganglia involvement, however some potentially helpful distinguishing features include cortical thickening and involvement of mesial temporal lobes and limbic systems [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the top differential considerations in BTBGD is viral encephalitis, particularly Ebstein-Barr virus which also demonstrates multifocal cortical, subcortical, and bilateral deep grey matter T2-FLAIR hyperintensities [8] . Autoimmune-mediated etiologies of encephalitis can also present with bilateral basal ganglia involvement, however some potentially helpful distinguishing features include cortical thickening and involvement of mesial temporal lobes and limbic systems [ 8 , 9 ]. Another important differential consideration is mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS), which clinically presents very similarly to BTBGD with a relapsing-remitting course, seizures, encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These disorders have the common neuroradiological feature of signal hypointensity of the basal ganglia on specific MR sequences known to demonstrate the magnetic resonance phenomenon of susceptibility which indicates excess mineralization (T2-weighted, T2*-weighted, susceptibility-weighted and echo-planar imaging b0-diffusion imaging data sets) [ 1 ] with some disorders also clearly associated with neuropathological findings of iron accumulation on post-mortem analysis. Over time, it is increasingly apparent that such radiological features are associated with a broad spectrum of neurological and neurodegenerative disorders including the mitochondrial cytopathies, genetic dystonias (such as those due to KMT2B and VPS16 mutations) and lysosomal disorders (GM1 gangliosidosis, alpha fucosidosis) [ 2 3 4 5 ], although for many of these disorders, correlation with post-mortem studies is not yet reported. As a result, precise classification of what comprises an NBIA disorder remains uncertain.…”
Section: Introductionmentioning
confidence: 99%